SCHOOL TECHNOLOGIES ОF PRESERVING STUDENTS' HEALTH: GENERAL CLASSIFICATION - Hlinchuk, Yuliia (Educological discourse, 2020)
The rapid loss of health of the younger generations during school education makes it a pressing problem for students to maintain their health during the learning process. This problem is extremely important not only for the general education environment but also for institutions of higher and postgraduate education, since the safety of the educational process for the health of students depends first and foremost on the teacher. However, to date, the problem of student health technologies has not been sufficiently studied. In particular, there is no single approach to the name and overall classification of such technologies. The article analyzes the views of scientists on the nature of student health technologies. Based on this, the term "school technologies of preserving students' health" and a general classification of student health preservation technologies are proposed for use, which logically integrates existing semantic interpretations. We believe that it is appropriate to separate school technologies for preserving students' health into appropriate health (technologies implemented in the educational process without compromising the health of the subjects: taking into account individual, age, gender characteristics; ergonomic, technical, organizational norms educational process, etc.) and health-saving (technologies aimed at shaping students' competences in maintaining their own health and that of other people: fostering a culture of health, health of the same lifestyle, sanogenic thinking etc.). It is noted that the results of theoretical analysis of the problem of general classification of school technologies of preserving students' health actualize the problem of further detailed classification of these technologies and ways of their introduction in the educational process of general educational institutions.